2008
DOI: 10.1071/fp07281
|View full text |Cite
|
Sign up to set email alerts
|

Growth, nutrition, and soil respiration of a mycorrhiza-defective tomato mutant and its mycorrhizal wild-type progenitor

Abstract: Abstract. The effects of colonisation of roots by arbuscular mycorrhizal fungi (AMF) on soil respiration, plant growth, nutrition, and soil microbial communities were assessed using a mycorrhiza-defective tomato (Solanum lycopersicum L.) mutant and its mycorrhizal wild-type progenitor. Plants were grown in rhizocosms in an automated respiration monitoring system over the course of the experiment (79 days). Soil respiration was similar in the two tomato genotypes, and between P treatments with plants. Mycorrhiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 58 publications
4
20
0
Order By: Relevance
“…Therefore, it seems possible that the greatest AMF abundance in the root system of 'Chondrolia Chalkidikis' infl uenced negatively root growth over that of shoot, and consequently infl uenced positively the ratio SDW/RDW. Cavagnaro et al (2008) found that AMF colonization of Solanum lycopersicum plants decreased root biomass, something which partially agrees with our data for olive plants, since, in each of the three soil types studied, 'Chondrolia Chalkidikis' had the lowest root biomass values (Table 3). Mycorrhizal maize plants had lower root to shoot ratios, than the non-mycorrhizal ones (Sheng et al, 2009).…”
Section: -------------------------------------------------G Dry Weigsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, it seems possible that the greatest AMF abundance in the root system of 'Chondrolia Chalkidikis' infl uenced negatively root growth over that of shoot, and consequently infl uenced positively the ratio SDW/RDW. Cavagnaro et al (2008) found that AMF colonization of Solanum lycopersicum plants decreased root biomass, something which partially agrees with our data for olive plants, since, in each of the three soil types studied, 'Chondrolia Chalkidikis' had the lowest root biomass values (Table 3). Mycorrhizal maize plants had lower root to shoot ratios, than the non-mycorrhizal ones (Sheng et al, 2009).…”
Section: -------------------------------------------------G Dry Weigsupporting
confidence: 81%
“…However, the greatest total plant weight, which was that of 'Kothreiki', coincided with the lowest AMF abundance found in the root system of that cultivar in each of the three soil types (Table 2), while the lowest total dry weight of plants, which was that of 'Chondrolia Chalkidikis', coincided with the greatest AMF abundance in its root system (Tables 2 and 3). Ducic et al (2008) found that the colonization of two P. menziesii cultivars with R. subareolatus suppressed plant growth, despite positive effects of mycorrhizas on plant P nutrition, while Cavagnaro et al (2008), Xiao et al (2010) and Orfanoudakis et al (2004) found that AMF colonization did not affect the above ground biomass of S. lycopersicum, rice and Alnus glutinosa plants, respectively, compared to the control ones. According to Sudova (2009), plant growth response of fi ve stoloniferous species to AMF inoculation with three species of Glomus varied widely from negative to positive.…”
Section: -------------------------------------------------G Dry Weigmentioning
confidence: 99%
“…Separation of the experimental variants in 3 clusters highlights strongly the difference of reactions of the varieties to fertilisation in conventional and unconventional culture system, similar to reported results by Liu et al (2014). Using conventional and unconventional treatments do not set strongly different developments, the 3 varieties having a homogenous response to these actions, as reported by Cavagnaro et al (2006Cavagnaro et al ( , 2008.…”
Section: Discussionsupporting
confidence: 77%
“…Much of the transcriptional response to the mycorrhizal symbiosis is likely a consequence of this additional mycorrhizal Pi uptake (Nagy et al 2009). Mycorrhizal plants also exhibit higher levels of mineral nutrients including sulfur (S), zinc (Zn), and copper (Cu) (Cavagnaro et al 2008;Liu et al 2000); however the plant transporters responsible for the uptake of these mycorrhizal-supplied nutrients have not been identified beyond transcriptional studies in greenhouse-grown plants (Guether et al 2009a). …”
Section: Introductionmentioning
confidence: 99%